Peranan kualitas laporan keuangan : kinerja perusahaan dan tata kelola perusahaan (GCG) dengan Sistem informasi keuangan Sebagai moderating - Alpi, M Firza; Ardiansa, Kiki; Rangkuti, Muhammad Ihsan (-, 2023)
This study aims to test and analyze the effect of good corporate governance and company performance on the quality of financial statements with accounting information systems as moderating variables at PT. Nusantara IV Medan Plantation. This study used a quantitative approach with an associative design. Data collection is carried out by collecting primary data in the form of questionnaires by distributing questionnaires to employees of the accounting and finance department at PT. Nusantara IV Medan Plantation.. The sample technique used in the study used saturated samples with the number of samples obtained as many as 40 samples. The data analysis technique used to test the hypothesis in this study is Multiple Linear Regression Analysis with the help of IBM SPSS software version 29. The results of this study show that good corporate governance has a positive and significant effect on the quality of financial statements. The company's performance has a negative and insignificant effect on the quality of financial statements, the accounting information system significantly moderates the effect of good corporate governance on the quality of financial statements, and the accounting information system does not moderate the effect of company performance on the quality of financial statements.